PENYULUHAN PENETAPAN HARGA POKOK PRODUKSI BARANG PADA KEGIATAN MARKET DAY SEKOLAH RABBANI JAKARTA - Desy Amaliati Setiawan; Muhammad Yusuf; Apry Linda Diana; Irfan Arif Husen (Bajang Institute, 2025)
Market Day is an activity held at schools or other educational institutions, where students are given the opportunity to sell products or services they have created themselves. This activity typically aims to develop entrepreneurial skills, creativity, and student independence It is expected to provide students with a significant understanding of the concept of cost of goods manufactured, the ability to calculate the cost of goods sold, increase the success of Market Day activities through careful pricing planning, and foster student interest in entrepreneurship. This outreach activity targets students at Rabbani School Jakarta, located on Jl. Pemuda, Rawamangun, East Jakarta. The estimated number of participants is approximately 50. The objectives of this activity are to improve student skills, build self-confidence, and increase parental involvement. This community service activity takes the form of outreach on determining the cost of goods manufactured during the Rabbani School Jakarta Market Day. The estimated number of participants is approximately 50. The outreach method is a process/method of providing information to others so they can understand and comprehend the material presented